Cover Picture: Fabrication of Fully‐Spray‐Processed Organic Photovoltaic Modules by using an Automated Process in Air (Energy Technol. 12/2013). Issue 12 (December 2013) - La Notte, Luca; Mineo, Daniel; Polino, Giuseppina; Susanna, Gianpaolo; Brunetti, Francesca; Brown, Thomas M.; Di Carlo, Aldo; Reale, Andrea
<x xml:space="preserve">Abstract</x> Spray‐Processing Photovoltaics—A Coating For All: The cover image illustrates the first example of an organic photovoltaic device that is fully fabricated by spray coating onto a transparent conductive oxide. The goal has been reached by using an automated, compact apparatus able to perform spray processes in air. The Full Paper from Andrea Reale and colleagues on page 757 details the technological steps adopted at the Center for Hybrid and Organic Solar Energy (CHOSE) of University of Rome "Tor Vergata" and shows the appealing electrical results of the devices. Fully sprayed modules open the way to expand the application of photovoltaics to almost anywhere, thanks to the conformability of spray coating to virtually any kind of substrate. By addint the property of semitransparency, the range of possible applications gets even broader, from building‐integrated photovoltaics to automotive or consumer electronics. <boxed-text content-type="graphic" position="anchor" orientation="portrait"> </boxed-text>